Диагностическая эффективность дентальной объемной томографии в эндодонтии (LLC "Endo Press", 2020)
Radiological methods are an important component in algorithm of patient examination in endodontic treatment. Hi-tech methods, such as cone beam dental tomography, allow more precisely to plan the given kind of treatment, and to supervise efficiency of spent medical actions in comparison with traditional radiological techniques. Introduction of cone beam dental computer tomography in dentistry practice gives the chance to lower quantity of complications and to raise quality of treatment.